Hubungan Penerimaan Informasi Melalui Pemberitaan Media Elektronik tentang Covid-19 dengan Tingkat Kecemasan Ibu Hamil - Ni Made Mastini Padmi; I Dewa Ayu Ketut Surinati; Suratiah Suratiah (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2023)
Corona Virus Disease (COVID-19) is a disease caused by the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-Cov-2) virus. One of the high risks of contracting Covid-19 is in pregnant women. The purpose of this study was to determine the relationship between receiving information through electronic media reporting about Covid-19 and the anxiety level of pregnant women in the UPTD Puskesmas Gianyar I Work Area. This type of research is quantitative analytic correlation with a cross-sectional using a total sampling technique. The number of samples in this study were 103 pregnant women according to the inclusion criteria. Statistical testing using Spearman's rank. Characteristics of pregnant women during the Covid-19 pandemic in the Working Area of the UPTD Health Center Gianyar I, pregnant women aged 20 to 35 years were 94 people (91.3%), pregnant women with high school education were 55 people (53.4%) and mothers 65 people (63.1%) had multigravida pregnancies. Receiving information through electronic media coverage is mostly good as many as 55 people (53.4%). The anxiety level of pregnant women has a mild anxiety level of 31 people (30.1%). Receiving information through electronic media coverage about Covid-19 and the anxiety level of pregnant women is significantly related to p = 0.002 (p 0.05). The conclusion in this study is that there is a significant relationship between receiving information through electronic media reporting about Covid-19 and the anxiety level of pregnant women according to the research results obtained. So, it is advisable to increase education about pregnancy care, especially pregnancy during the Covid-19 period and counseling and assistance programs for pregnant women.